Photocatalytic Degradation of Methylene Blue and Methyl Orange by Y-PTC Metal-Organic Framework - Adawiah Adawiah; Muhammad Derry Luthfi Yudhi; Agustino Zulys (Syarif Hidayatullah State Islamic University, 2021)
The yttrium based metal-organic framework (MOF) Y-PTC was synthesized by the solvothermal method using perylene as the linker and yttrium as metal ion. This study aims to assess the photocatalytic activity of yttrium-perylenetetracarboxylate (Y-PTC) metal-organic framework (MOF) toward methylene blue and methyl orange under visible light irradiation. The results of the FTIR analysis showed that Y-PTC MOF had a different structure and composition from its precursor (Na4PTC). The Y-PTC MOF has a bandgap energy value of 2.20 eV with a surface area of 47.7487 m2/g. The SEM-EDS analysis showed an elemental composition of yttrium, carbon, and oxygen, were 6.9%, 72.1% and 20.7%, respectively. Furthermore, Y-PTC MOF was able to adsorb dyes at the optimum by 78.10% and 35.57% toward methylene blue (MB) and methyl orange (MO) at the dispersion period of 60 mins. Y-PTC MOF exhibited photocatalytic activity towards the degradation of methylene blue and methyl orange under visible light irradiation. The addition of H2O2 inhibited Y-PTC photocatalytic activity towards MO degradation from 50.89% to 26.38%. In contrast to MO, the addition of H2O2 had a positive effect on MB, which increased the degradation from 87.56% to 91.65%. Therefore, Y-PTC MOF possessed the potential of a photocatalyst material in dyes degradation under visible light irradiation.